Management of early gastric cancer with positive horizontal or indeterminable margins after endoscopic submucosal dissection: multicenter survey - Ishii, Naoki; Omata, Fumio; Fujisaki, Junko; Hirasawa, Toshiaki; Kaise, Mitsuru; Hoteya, Shu; Tanabe, Satoshi; Ishido, Kenji; Ohata, Ken; Takita, Maiko; Mine, Tetsuya; Igarashi, Muneki; Yoshida, Tatsuya; Takeda, Yuichi; Furumoto, Yohei; Matsumoto, Kenshi; Yahagi, Naohisa; Nakashima, Hirotaka; Wada, Tomonori; Tagata, Tomoko; Mitsunaga, Atsushi (Endoscopy International Open, 2017)
Background and study aims Positive horizontal margins in resected specimens are sometimes encountered after endoscopic submucosal dissection (ESD) for early gastric cancers, and appropriate treatment strategies for these cases are not established. The aim of this study was to evaluate current empirical treatments for patients with positive horizontal or indeterminable margins after ESD.Patients and methods We performed a multicenter survey and data from 14 hospitals were collected. The pooled proportions of positive horizontal or indeterminable margins and those of patients followed up without early intervention were calculated using a logistic-normal random-effects model. For calculating pooled estimates, subgroup analyses of high- and non-high-volume centers were conducted. Results A total of 11,796 ESD cases were enrolled and 229 patients (2 %) had positive horizontal or indeterminable margins. Ninety-eight cases were treated within 30 days of ESD and 131 cases were followed up without early treatments. Pooled estimates of positive margins in high- and non-high-volume centers were 1 % (95 % CI: 1 % – 2 %) and 2 % (95 % CI: 1 % – 4 %), respectively, and were not heterogeneous (P = 0.191). The proportion of patients followed up without early intervention ranged from 30 % to 100 %. The pooled estimate was 68 % (95 % CI: 50 % – 83 %). The pooled estimates of high- and non-high-volume centers were 65 % (95 % CI: 38 % – 85 %) and 72 % (95 % CI: 44 % – 89 %), respectively, and were not heterogeneous (P = 0.692).Conclusion There was insufficient consensus regarding treatment strategies used for early gastric cancer with positive horizontal or indeterminable margins after ESD. Further studies are required to establish a consensus.